Otoacoustic Emissions for Outcome Prediction in Postanoxic Brain Injury - Kondziella, Daniel; Jensen, Anne Marie; Hjuler, Thomas; Bille, Michael; Kjaergaard, Jesper (Frontiers in Neurology, 2018)
Background. Non-invasive, easy-to-use bedside tools to estimate prognosis in unresponsive patients with post-anoxic brain injury are needed. We assessed the usefulness of otoacoustic emissions as outcome markers after cardiac arrest. Methods. Distortion product otoacoustic emissions (DPOAE) and transient evoked otoacoustic emissions (TEOAE) were measured in cardiac arrest patients whose prognosis was deemed to be poor following standard neurological assessment (n=10). Ten patients with myocardial infarction without prior loss of consciousness served as controls. Results. Compared to controls with myocardial infarction, cardiac arrest patients with poor neurological prognosis had significantly less often preserved DPOAE (9.2% vs. 40.8% positive measurements; OR 0.15 (CI 0.07-0.30); p < 0.0001)). Partially preserved DPOAE were noted in 4 cardiac arrest patients. TEOAE were not statistically different between the two groups. Conclusions. Despite their convenience, otoacoustic emissions cannot be used as reliable prognostic markers in cardiac arrest survivors. This is because we identified 4 cases with partially preserved otoacoustic emissions in a sample of 10 unresponsive post-cardiac arrest patients whose neurological condition was so poor that active treatment was withdrawn. However, we suggest that future research should address if decaying outer hair cell function over time may serve as a proxy for evolving ischemic brain damage.